2011
DOI: 10.1007/s10682-011-9492-8
|View full text |Cite
|
Sign up to set email alerts
|

New phylogenetic information suggests both an increase and at least one loss of cooperative breeding during the evolutionary history of Aphelocoma jays

Abstract: Efforts to identify ecological and life history factors associated with cooperative breeding have been largely unsuccessful, and interest is growing in the role of phylogenetic history in determining the distribution of this social system among lineages. In birds, cooperative breeding is distributed non-randomly among lineages, suggesting that phylogenetic inertia may play an important role in determining its distribution. The bird genus Aphelocoma has been particularly well studied because, although it is a r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…Although it is difficult to test this hypothesis directly, recent phylogenetic analyses have revealed several examples of complex social groups with low genetic relatedness that have evolved from lineages with a phylogenetic history of cooperation in smaller, kin-based groups [60] (electronic supplementary material, table S2). For example, the crows and jays (Corvidae) are a large clade in which family cohesiondelayed dispersal of offspring and the formation of stable family groups-appears to be an ancestral behaviour.…”
Section: What Are the Evolutionary Origins Of Non-kin Cooperation?mentioning
confidence: 99%
“…Although it is difficult to test this hypothesis directly, recent phylogenetic analyses have revealed several examples of complex social groups with low genetic relatedness that have evolved from lineages with a phylogenetic history of cooperation in smaller, kin-based groups [60] (electronic supplementary material, table S2). For example, the crows and jays (Corvidae) are a large clade in which family cohesiondelayed dispersal of offspring and the formation of stable family groups-appears to be an ancestral behaviour.…”
Section: What Are the Evolutionary Origins Of Non-kin Cooperation?mentioning
confidence: 99%
“…Here we test for microgeographic divergence in bill morphology in a New World jay (genus Aphelocoma ). This clade of birds has served as a model system for the study of evolutionary diversification because there are a wealth of examples documenting intra‐ and interspecific variation in ecological niche space (Rice et al ; McCormack et al ), social and breeding systems (Woolfenden and Fitzpatrick ; Berg et al ), and morphological traits (Pitelka ; Peterson ; McCormack and Smith ). Morphological changes have also occurred in association with transitions between habitat types.…”
mentioning
confidence: 99%
“…As the common ancestor of species in the Aphelocoma genus was likely social, it is possible that cognitive abilities like social learning were not lost when CASJ lost sociality 66 69 . In fact, species in the Aphelocoma genus notably exhibit wide variation in social behavior, indicating that it is a fairly plastic trait 70 .…”
Section: Discussionmentioning
confidence: 99%
“…In fact, species in the Aphelocoma genus notably exhibit wide variation in social behavior, indicating that it is a fairly plastic trait 70 . The most supported phylogenetic tree indicates the common ancestor of Aphelocoma species was likely a singular cooperative breeder 68 , 69 with a breeding system similar to that of the extant Florida scrub-jay ( A. coerulescens ) where young delay dispersal to help their parents raise siblings in subsequent breeding attempts. Research on juvenile Florida scrub-jays revealed they possess the ability to socially learn from parents about foraging opportunities in a novel patch 71 .…”
Section: Discussionmentioning
confidence: 99%